Simulation of movements of cargo with a flat base on a four-axle platform - Saidivaliev Shukhrat; Djabbarov Shukhrat; Abdullaev Bakhrom; Ortiqov Mironshox; Rustamov Nassim (E3S Web of Conferences, 2023)
The improvement of the methodology for calculating the tension in the flexible elements of cargo fasteners with the simultaneous action of longitudinal, lateral and vertical forces on the "fastening-cargo" subsystem of the mechanical system "path - wagon – fastening - cargo" and during the movement of rolling stock, both along a straight and curved section of the track should be aimed at ensuring safety the movement of trains, safe transportation of goods on route and to ensure the safety of transport structures (vibration towers of power lines, railway bridges, etc.). There is still no mathematical model that would directly determine the tension in the flexible elements of the cargo fasteners and determine the location of the thrust bar to ensure the joint operation of the flexible and thrust elements of the fasteners.